Leveraging Influence on the UN Security Council: The Cases of Brazil, India, and South Africa*1 - Aguilar, Sérgio Luiz Cruz [UNESP] (FapUNIFESP (SciELO), 2025)
There is always scepticism about the extent to which an elected member of the United Nations Security Council (UNSC) can meaningfully exert influence. This article reassesses how, between 2010 and 2012, Brazil, India, and South Africa tried to leverage their membership to influence UNSC decision-making processes. It addresses the Council’s dynamics and practices, the centrality of its five permanent members (P5), and the ways these countries achieve their foreign policy objectives. Through country-specific cases, this article shows that although there is space for an elected member to influence the Council, challenging the predom-inance of the P5 remains difficult, even by seizing opportunities and engaging with key UNSC players.
Aprovechar la Influencia en el Consejo de Seguridad de la ONU: Los Casos de Brasil, India y Sudáfrica
Renforcer l’Influence au Conseil de Sécurité de l’ONU: Les Cas du Brésil, de l’Inde et de l’Afrique du Sud
Keywords: Brazil; elected members’ influence; India; South Africa; UN Security Council